Organizational Dysfunctions of Decline - Cameron, Kim S.; Whetten, David A.; Kim, Myung U. (Academy of Management Journal, 1987)
The article discusses the dysfunctional attributes of organizations experiencing periods of decline. Organizations involved in the study were gauged using a number of dysfunctional attributes in organizations identified by scholars, including the centralization of decision making, a lack of long-term planning and a pronounced decrease in the adoption of innovations. According to the author, the aforementioned attributes are characteristic of both stable and declining organizations. Only organizations experiencing growth in revenues seem to avoid these problems.